2016
DOI: 10.1159/000450701
|View full text |Cite
|
Sign up to set email alerts
|

Correlation or Limits of Agreement? Applying the Bland-Altman Approach to the Comparison of Cognitive Screening Instruments

Abstract: Background/Aims: Calculation of correlation coefficients is often undertaken as a way of comparing different cognitive screening instruments (CSIs). However, test scores may correlate but not agree, and high correlation may mask lack of agreement between scores. The aim of this study was to use the methodology of Bland and Altman to calculate limits of agreement between the scores of selected CSIs and contrast the findings with Pearson's product moment correlation coefficients between the test scores of the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Using the datasets of several pragmatic diagnostic test accuracy studies undertaken in a secondary care Cognitive Function Clinic (Abdel‐Aziz and Larner ; Larner , ), regression equations of the form y = a + bx were calculated, where y , the dependent or outcome variable, was approximate MMSE score; x , the independent or explanatory variable, was score on different CSIs with which MMSE was being compared, namely Montreal Cognitive Assessment (MoCA), Mini‐Addenbrooke's Cognitive Examination (MACE), Six‐item Cognitive Impairment Test (6CIT) and the informant AD8; and a is the intercept and b the slope or gradient (regression coefficient) of the regression equation. Pearson product moment correlation coefficients were also calculated (Table ).…”
Section: Regression Equations and Correlation Coefficients Of Mmse Anmentioning
confidence: 99%
“…Using the datasets of several pragmatic diagnostic test accuracy studies undertaken in a secondary care Cognitive Function Clinic (Abdel‐Aziz and Larner ; Larner , ), regression equations of the form y = a + bx were calculated, where y , the dependent or outcome variable, was approximate MMSE score; x , the independent or explanatory variable, was score on different CSIs with which MMSE was being compared, namely Montreal Cognitive Assessment (MoCA), Mini‐Addenbrooke's Cognitive Examination (MACE), Six‐item Cognitive Impairment Test (6CIT) and the informant AD8; and a is the intercept and b the slope or gradient (regression coefficient) of the regression equation. Pearson product moment correlation coefficients were also calculated (Table ).…”
Section: Regression Equations and Correlation Coefficients Of Mmse Anmentioning
confidence: 99%
“…Some comparisons of different cognitive tests have used the Bland-Altman approach originally developed to assess agreement between tests measuring the same unit (i.e., mL/min). This approach was recently applied to assess agreement between the total scores on the MMSE, MoCA, and Addenbrooke's Cognitive Exam Revised (ACE-R) [24]. An earlier study applied the Bland-Altman approach to assess agreement between total scores on a longer cognitive test, the ADAS-Cog, with the MMSE and CDR using standardized scores given variability in ranges across the tests [25].…”
Section: Discussionmentioning
confidence: 99%
“…In a nephrology clinic cohort of patients with chronic kidney disease and diabetes (n = 112), the sensitivity and specificity for a dementia diagnosis were 0.96 and 0.84, respectively, at the cut point < 25/30 [6]. Studies in a dedicated cognitive disorders clinic have suggested superiority of the MACE to MMSE [7][8][9] and single-item cognitive screening questions [10] and equivalence to the Montreal Cognitive Assessment (MoCA) [9,11,12], and a better performance in those aged > 65 years, with a higher prevalence of cognitive impairment [13]. In a study of patients with mild AD (n = 92) and healthy controls (n = 68), MACE had an area under the receiver operating characteristic (AUC ROC) curve of 0.939, which was superior to ACE-III (0.897), Rowland Universal Dementia Assessment Scale (0.889), MMSE (0.874), Memory Impairment Screen (0.866), and MoCA (0.856) [14].…”
Section: Introductionmentioning
confidence: 99%